2016
DOI: 10.1158/2159-8290.cd-15-0583
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin-Targeted CARs: Driving T Cells to Solid Tumors

Abstract: Chimeric antigen receptors (CARs) are synthetic receptors that target T cells to cell-surface antigens and augment T-cell function and persistence. Mesothelin is a cell-surface antigen implicated in tumor invasion, which is highly expressed in mesothelioma, lung, pancreas, breast, ovarian, and other cancers. Its low-level expression in mesothelia however commands thoughtful therapeutic interventions. Encouragingly, recent clinical trials evaluating active immunization or immune-conjugates in patients with panc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
322
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(345 citation statements)
references
References 120 publications
4
322
0
Order By: Relevance
“…53 In addition, studies on genetically modified T cells with CARs, including anti-mesothelin CAR T cells, report significant efficacy in different malignancies. 54,55 This membrane-bound antigen specificity could be of interest for generating anti-mesothelin CAR T cells using one of these discriminating Fabs.…”
Section: Discussionmentioning
confidence: 99%
“…53 In addition, studies on genetically modified T cells with CARs, including anti-mesothelin CAR T cells, report significant efficacy in different malignancies. 54,55 This membrane-bound antigen specificity could be of interest for generating anti-mesothelin CAR T cells using one of these discriminating Fabs.…”
Section: Discussionmentioning
confidence: 99%
“…In phase I studies, SS1P generated neutralizing antibodies to the pseudomonas endotoxin (PE) (51,52); therefore, in a subsequent study, pentostatin and cyclophosphamide were given before the administration of SS1P to deplete T and B lymphocyte, thus delaying the A phase I study to assess the maximum tolerated dose and the immunogenicity of RG778 is currently under way in MPM patients (NCT02798536). (IV) Mesothelin CARs: adoptive T cell therapy using engineered T cells directed towards tumor antigens (CAR-T) is another promising approach that has shown impressive clinical outcomes in leukemia, and it is now being investigated in solid malignancies (55). Mesothelin is an especially appealing target for this approach since it is overexpressed in the majority of MPM, and several preclinical and clinical studies have found that is involved in tumorigenesis, as well as being associated with tumor aggressiveness (56).…”
Section: Immune-targeting Of Mesothelinmentioning
confidence: 99%
“…[84] Efforts to identify highly specific tumor antigen is required to minimize the on target-off tumor effects. [85] At present, TCR therapy against NY-ESO antigen for advanced synovial sarcoma in LA-A*201, HLA-A*205, or HLA-A*206 allele-positive patients has been granted breakthrough therapy designation by the FDA. [86,87] …”
Section: Tcr Therapymentioning
confidence: 99%